Implementation of occupational safety and health management system in reducing ergonomic risk among certified and uncertified automotive industry workers - Ikpegbu, Mavis Amarachi (2015)
Risk management in an integrated way, using organization’s operations has become highly important in recent years, since it not only cuts accident rates but can also improve the firm’s productivity, economic and financial results. Work-related injuries and occupational diseases have become an increasing concern to employees, employers, and governments because of its big impacts on workers’ health and productivity. Occupational Safety and Health Management System (OSHMS) is a planned, documented and verifiable method of managing hazards and associated risks in work place. OSHMS provides a set of tools that enhance safety, risk management efficiency related to all organization’s activity, it is a systematic means for employers to handle challenges and reduce haphazard attitudes to risk and problems in the work environment. In Malaysia, there is paucity of reports on risk factors among automotive factory workers because comprehensive studies in determining the risk factors have not been done in manufacturing industries. Therefore the aim of this research was to compare the implementation of occupational safety and health management system in reducing ergonomics risk among workers at a certified and uncertified automotive manufacturing industry. Data was collected by using a questionnaire survey, which was adopted from MSOSH and was integrated with the Nordic Questionnaire for MSD and the workers were also observed using the Quick Exposure Check (QEC) guidelines among 400 workers in both OSHMS certified and uncertified automotive industries located in Klang Valley, Malaysia. The data generated was statistically analyzed using SPSS version 21.0 and the finding revealed that workers in OSH certified company had a significant lower score for back posture of 14.07±1.584 compared to the workers in uncertified company 15.49±1.566, also mean values of shoulder/arm posture,wrist/hand postures and neck posture among the workers of the OSH certified company were 15.95±2.219, 15.48±1.190 and 7.13±1.053 respectively, which was significantly lower compared to the workers of the uncertified automotive company, who scored 18.94±1.943, 16.29±1.123 and 7.82±0.574, respectively. Also the ergonomics risk, occupational hazards, environmental management and OSH mean score value of workers in occupational safety and health certified company was significantly higher (p < 0.05)at 70.48±6.56, 55.77±8.72, 54.54±7.43 and 67.53±7.00 compared to the mean value scored by workers in OSH uncertified company, which was 64.66±4.11, 50.26±9.26, 51.35±4.52, 55.11±3.98. Chi square (χ2) test also showed that the studied variables (ergonomics risk factors management, occupational hazard management, environmental management and occupational safety and health procedures) were significantly (p < 0.05) associated with workers working in OSHMS certified company. Logistic regression test indicated that there is significant negative relationship between the ergonomics risk factors with the workers working in OSH certified and uncertified automotive industry. Also linear regression test revealed that there is a significant relationship between ergonomics risk and demographic factors. Therefore certification fosters the implementation of OSHMS among workers.